Integrated crop management in potato through farmers’ field school with special reference to women (The Journal of Plant Protection Sciences, 2022)
Integrated Crop Management (ICM) study was done in 16 locations of 4 districts of Bangladesh with different po tato varieties during 2009-10 and 2010-2011 potato growing seasons to find out the profitability level of ICM prac tice with farmers’ practice. A study plot was set up in each location where Integrated Crop Management (ICM)  practices recommended by the Tuber Crops Research Centre (TCRC) of BARI was followed in half of the plot and  in the other half, Farmers’ conventional Practices (FP) were followed. It was found in all locations that there were  distinct differences between the ICM practice and the FP in respect of yield. In all locations except those of Bogra,  farmers used fertilizers in higher doses than the recommended doses. Insecticides were not used even in the seed  production plots in most of the study areas but fungicides were used in more than the recommended quantity re sulting in misuse and environmental hazards. All farmers obtained lower yields in their practices than the ICM  method. Incidences of different diseases were found to be higher in the FP plots than those of the ICM. Boric acid  and bleaching powder had a positive effect in controlling scab and wilt, respectively. The farmers of Bogra and  Comilla are likely to be benefited more by practicing ICM than those of the other districts. Benefit-Cost Ratio was  higher in Munshiganj for ICM practice (2.77) on total cost basis and in Bogra for farmers’ practice (4.63) on cash  cost basis. Moreover, participating women members of Farmers’ Field School (FFS) became economically bene fited by making and selling potato chips that might leads them towards empowerment and social dignity.
Keywords: Farmers; Field School; potato ICM; women participation; Bangladesh